2018
DOI: 10.1111/jcpe.13031
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of Miller class I and II recessions treatment with the use of modified coronally advanced tunnel technique with either collagen matrix or subepithelial connective tissue graft: A randomized clinical study

Abstract: Aim To compare outcomes of modified coronally advanced tunnel technique (MCAT) combined with either collagen matrix (CM) or subepithelial connective tissue graft (SCTG) in the treatment of Miller class I and II multiple gingival recessions in the mandible. Materials and methods The study encompassed 91 recessions in 29 patients for whom MCAT was combined with CM on one side of the mandible and SCTG on the contralateral one. The following clinical parameters were measured: gingival recession height (GR) and wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
83
7

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 67 publications
(103 citation statements)
references
References 35 publications
11
83
7
Order By: Relevance
“…The age of the participants ranged from 18 to 50 years with a follow‐up period ranging from 3 months to 5 years. All included studies (Table ) compared CMX with CTG for the treatment of MAGR (Aroca et al, ; Cieślik‐Wegemund, Wierucka‐Młynarczyk, Tanasiewicz, & Gilowski, ; Pietruska, Skurska, Podlewski, Milewski, & Pietruski, ; Tonetti et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The age of the participants ranged from 18 to 50 years with a follow‐up period ranging from 3 months to 5 years. All included studies (Table ) compared CMX with CTG for the treatment of MAGR (Aroca et al, ; Cieślik‐Wegemund, Wierucka‐Młynarczyk, Tanasiewicz, & Gilowski, ; Pietruska, Skurska, Podlewski, Milewski, & Pietruski, ; Tonetti et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…All studies clearly included MAGR with Class I and II Miller's GR. Three studies involved both maxillary and mandibular teeth (Aroca et al, ; Cieślik‐Wegemund et al, ; Tonetti et al, ), whereas one study reported only mandibular teeth (Pietruska et al, ). The remaining did not mention which arches were treated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations